2022
DOI: 10.1038/s41598-022-09268-9
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in common marmoset gut microbiome associated with duodenal strictures

Abstract: Chronic gastrointestinal (GI) diseases are the most common diseases in captive common marmosets (Callithrix jacchus). Despite standardized housing, diet and husbandry, a recently described gastrointestinal syndrome characterized by duodenal ulcers and strictures was observed in a subset of marmosets sourced from the New England Primate Research Center. As changes in the gut microbiome have been associated with GI diseases, the gut microbiome of 52 healthy, non-stricture marmosets (153 samples) were compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The SUC group also showed reduction in possible bene cial genera such as Muribaculaceae, Oscillibacter, Faecalibaculum, Parasutterella, and Olsenella. Disease-associated genera in the SUC group, such as Clostridium sensu stricto 1, are found to have increased abundance in duodenal strictures subjects 37 and mice fed with a high-fat diet increase abundance of Lachnospiraceae UCG-006 38 . A potential bene cial genus in the SUC group: Muribaculaceae, a potential bene cial genus in the SUC group, is enriched in lean mice 39 and may be involved in the degradation of complex carbohydrates 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The SUC group also showed reduction in possible bene cial genera such as Muribaculaceae, Oscillibacter, Faecalibaculum, Parasutterella, and Olsenella. Disease-associated genera in the SUC group, such as Clostridium sensu stricto 1, are found to have increased abundance in duodenal strictures subjects 37 and mice fed with a high-fat diet increase abundance of Lachnospiraceae UCG-006 38 . A potential bene cial genus in the SUC group: Muribaculaceae, a potential bene cial genus in the SUC group, is enriched in lean mice 39 and may be involved in the degradation of complex carbohydrates 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Megamonas was also reported to be related to obesity and Crohn’s disease patients in humans [ 41 , 42 ]. In marmosets, Megamonas was abundant in IBD progressors and duodenal strictures [ 16 , 43 ]. Future detailed studies of the physiological characteristics of the animals from each vendor will reveal the biological significance of the bacterial genera that characterize animals from these vendors and their potential involvement as experimental animals in the reproducibility of in-vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…RF-based model and ANCOM-BC test can be used together to determine the reliable biomarkers for indicating PS and PQ. Sheh et al (2022) reported that RF-based models were the most accurate models and correctly classified strictures indicators for chronic gastrointestinal diseases using 9 ASVs 54 . Based on the RF-based model and ANCOM results, Clostridium perfringens was identified as a potential causative agent associated with the development of strictures.…”
Section: Discussionmentioning
confidence: 99%